The Clinician Faced With Anticochlear Antibodies: What to Do With Them?. Issue 3 (April 2018) - Carlomagno, Adriana; Silveira, Gonzalo; Rebella, Martín; Vola, Magdalena; Danza, Alvaro
Abstract : Background: Autoimmune inner ear disease as a cause of sensorineural hearing loss is a poorly understood entity. Thus, the role of anticochlear antibodies (ACLAs) in clinical management is still not well established. Objective: The aims of this study were to describe the use of ACLAs in our clinical setting and to understand the clinicians' therapeutic approach in these cases. We also analyzed the usefulness of these autoantibodies in clinical practice. Methods: A retrospective study with nonprobabilistic convenience sampling of patients who were tested for ACLAs in the period from January 1, 2013, to December 31, 2015, was performed. The study was carried out in 2 stages: (1) medical records of all patients who were investigated for ACLAs were reviewed. The following variables were analyzed: age, sex, reason for requesting ACLAs, concomitant autoimmune disease, audiogram, immunosuppressive treatment, duration of treatment, and clinical response; (2) patients who received immunosuppressive therapy were contacted by telephone. A visual analog scale (VAS) (0–10) was applied to evaluate the therapeutic response. Results: Thirty-nine patients who were investigated for ACLAs were identified. The mean age was 41 (SD, 16) years; there were 33 female patients. Of the 34 patients with ACLA-positive antibodies, 16 patients received immunosuppressive agents, of for management of their sensorineural hearing loss, corticosteroids was the most commonly used treatment. No clinical improvement was reported by patients after immunosuppressive treatment in this subgroup. Conclusions: The role of ACLAs in the diagnosis and management of sensorineural hearing loss remains unclear. In this small study at a single institution, ACLA testing may not have improved the outcome of sensorineural hearing loss.